Factors influence studying at rural area and student’s academic performance / Nor Idayu Ros Almi - Almi, Nor Idayu Ros (2013)
This research is to identify the relationship between the factors that influence studying at rural area and student academic performance. This study is limited to the respondents at rural area and limited to IPT A students in Jengka. This study is limited to Bachelor Office Management's students in UiTM Jengka, Pahang and this study only focusing the factors influence studying at rural area and students' academic performance. There have been three factors that influence students' academic performance which are Technology, Facilities and Transportation. So, there is relationship between the factors influence studying a rural area towards student's academic performance. Technology is the factor that most influence students' academic performance and the lowest factor that affect students' academic performance among students in UiTM Jengka Pahang is facilities. Government, Educational Institution and for the future research recommend that, technology, facilities and transportation need to be developed well in order to improve students' academic performance.